Trajectory of crawl hand motion analyzed for elite age-group swimmers - Schmidt, A. C.; Ungerechts, B. E. (1st International Scientific Conference of Aquatic Space Activities, 2008)
judgment of arm motion below waterline based on observation from pool deck is not always sufficient to determine the effectivity of the action. For this purpose Reischle (1979) proposed to film the hand motion using fixed underwater cameras. Using one camera the 3-D-motion of the hand can be represented by a 2-D-trajectory in a plane; mostly the sagittal plane is represented and the components forwards / backwards and upwards / downwards can be investigated. Using a fixed camera instead of a panning one the hand motion resembles a cycloid shape (a curve generated by a curve rolling on another curve) with trocoid property, namely the exit point is in front of the entry point of the hand. This is the topographical basis of the interaction between hand and water, called water-view. A 2-D-trajectory can be analyzed quantitatively. The purpose of this paper is to compare the sagittal trajectory of age-group swimmers before and after an intervention and a 3rd time without intervention.